Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien di RSUD H. Padjonga Dg Ngalle Kabupaten Takalar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed  to determine the effect of service quality on patient satisfaction at H. Padjonga Dg. Ngalle Takalar Regency. This type of research used quantitative research with survey research types. The sample technique used  simple random sampling with research instrument measurements namely; Likert scale. The data analysis technique used descriptive statistical analysis techniques and simple regression analysis techniques used SPSS  26 version. The results of this study on the Effect of Service Quality on Patient Satisfaction showed that the regression coefficient (b) value was 15,254 which could be interpreted that the independent variable or Service Quality (X) had a positive or strong effect on the dependent variable or patient satisfaction (Y). Based on the results of t arithmetic> t table (15,254> 1,675) or significant (Sig) of 0,000 less than